EXPORTINGORGANIZED TEACHING DOCUMENTS FROM MINDMANAGER - Yosi Madsu; Dindin Ahmad Toharudin; Rayhanul Jannah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Mind map application can be utilized into a multi-document content editor by extending its functionality. Thus, authoring documents and their content can be done as easy as putting ideas on a mind map. Many studies use mind maps to deliver teaching materials or use it as a tool to learn materials, but the contents that already in the mind map are rarely to be maintained as a formal document. In this paper, steps to export organized teaching documents from MindManager by using macro and Latex class is explained. After extending mind map functionalities, creating course structures, contents, and materials is as easy as creating a mind map and its notes.